Recognising and responding to deteriorating patients: what difference do national standards make? - Matthew H. Anstey; Alice Bhasale; Nicola J. Dunbar; Heather Buchan (BMC Health Services Research, 2019)
Abstract Background The Australian Commission on Safety and Quality in Health Care released a set of national standards which became a mandatory part of accreditation in 2013. Standard 9 focuses on the identification and treatment of deteriorating patients. The objective of the study was to identify changes in the characteristics and perceptions of rapid response systems (RRS) since the implementation of Standard 9. Methods Cross-sectional study of Australian hospitals. Baseline data was obtained from a pre-implementation survey in 2010 (220 hospitals). A follow-up survey was distributed in 2015 to staff involved in implementing Standard 9 in public and private hospitals (276 responses) across Australia. Results Since 2010, the proportion of hospitals with formal RRS had increased from 66 to 85. Only 7% of sites had dedicated funding to operate the RRS. 83% of respondents reported that Standard 9 had improved the recognition of, and response to, deteriorating patients in their health service, with 51% believing it had improved awareness at the executive level and 50% believing it had changed hospital culture. Conclusions Implementing a national safety and quality standard for deteriorating patients can change processes to deliver safer care, while raising the profile of safety issues. Despite limited dedicated funding and staffing, respondents reported that Standard 9 had a positive impact on the care for deteriorating patients in their hospitals.